The Influence of Work Environment, Organizational Support, and Leadership on Work Discipline that Impacts the Performance of BUMDes Employees in Paninggaran Subdistrict, Pekalongan Regency - Agus Joko Santos, Devi manatika asti; Heri Prabowo; Shofif Sobaruddin Akbar (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This research aims to determine the influence of the work environment, organizational support, and leadership on work discipline, which impacts the performance of BUMDes employees in PaninggranSubdistrict, Pekalongan Regency. The study is conducted using a quantitative research method, with a questionnaire as the research instrument. The sample consists of 100 respondents, selected using a nonprobability sampling method and probability sampling technique, with the population being BUMDes employees across Paninggaran Subdistrict, Pekalongan Regency, totaling 100 respondents or employees. The research data were analyzed using the Structural Equation Modelling (SEM) statistical method with the Smart PLS 3 application. The research data have passed validity and reliability tests, indicating that the results comply with the model requirements to proceed to hypothesis testing. The findings of this study show that: (1) the work environment influences the performance of BUMDes employees in Paninggran Subdistrict, (2) organizational support influences the performance of BUMDes employees in Paninggran Subdistrict, (3) leadership influences the performance of BUMDes employees in Paninggran Subdistrict, (4) work discipline influences the performance of BUMDes employees in Paninggran Subdistrict, (5) the work environment influences work discipline among BUMDes employees in Paninggran Subdistrict, (6) organizational support influences work discipline among BUMDes employees in Paninggran Subdistrict, (7) leadership does not influence work discipline among BUMDes employees in Paninggran Subdistrict, (8) the work environment influences employee performance through work discipline among BUMDes employees in Paninggran Subdistrict, (9) organizational support influences employee performance through work discipline among BUMDes employees in Paninggran Subdistrict, (10) leadership does not influence employee performance through work discipline among BUMDes employees in Paninggran Subdistrict.